Corrosion-resistant photovoltaic reflective film and preparation method thereof

By using materials such as polyhydroxy polyethylene glycol and trimethylol propane diacrylate in the reflective film to generate a cross-linking agent containing double bonds and modifying the fluorocarbon coating, the bonding between the carrier film and the EVA film in the reflective film is solved. The problem of poor performance is achieved by achieving higher corrosion resistance and bonding performance.

CN119320507AInactive Publication Date: 2025-01-17JIANGSU SMART WORKSHOP TECHNOLOGY RESEARCH INSTITUTE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411518619.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing reflective film has poor bonding performance between the carrier film and the EVA adhesive film, which affects practical application.

Method used

Polyhydroxy polyethylene glycol, trimethylolpropane diacrylate or trimethylolpropane monoallyl ether are used to generate polyurethane acrylate cross-linking agent, combined with isophorone diisocyanate and dibutyltin dilaurate. Form a cross-linking agent containing double bonds, which is used to modify fluorocarbon coatings and improve the bonding performance of PET film and EVA film.

Benefits of technology

Significantly improves the corrosion resistance of fluorocarbon coatings and the bonding performance between PET film and EVA film, enhancing the practicality of the reflective film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005107414380000101
    Figure BDA0005107414380000101
Patent Text Reader

Abstract

The invention relates to the technical field of reverse films, in particular to a corrosion-resistant photovoltaic reflective film and a preparation method thereof. According to the scheme, a PET film serves as a carrier, one side of the PET film is coated with light-cured resin, rolling is conducted through a mold pressing roller, then light curing is conducted, a prism structure layer is formed, then metallic aluminum is plated on the prism structure layer to form a light reflecting layer, finally, the other side of the PET film is coated with fluorocarbon coating, and the light reflecting film is obtained after curing. The specific processing technology adopted in the preparation process is not limited, and only the technical effect of the invention can be realized; when the prism structure layer is actually processed, light-cured resin can also be coated on the surface of a die compression roller and then is transferred to the surface of the PET film to form a prism structure, the reflective layer can realize plating of a metal layer through processes of vacuum evaporation, magnetron sputtering, electroplating and the like, and plating materials can be selected from aluminum, silver and the like, so that the reflective effect is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of reverse film, in particular to a corrosion-resistant photovoltaic reflective film and a preparation method thereof. Background Art

[0002] Reflective film is a kind of retro-reflective material which can be directly used after being made into a thin film. According to the structure of the reflective unit of the reflective film, the reflective film is generally divided into two categories, namely glass bead type reflective film and micro-prismatic type reflective film. The reflective film is generally composed of a reflective layer, a reflective structure layer (prism or glass micro-bead), a carrier film, a fluorine-containing resin or a fluorine-containing coating, and an EVA film layer structure. However, in actual processing, the bonding performance between the carrier film and the EVA film is poor, which affects the actual application.

[0003] Based on this situation, the present application discloses a corrosion-resistant photovoltaic reflective film and a preparation method thereof to solve this technical problem. Summary of the invention

[0004] The object of the present invention is to provide a corrosion-resistant photovoltaic reflective film and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A method for preparing a corrosion-resistant photovoltaic reflective film comprises the following steps:

[0007] Step (1): Mix polyhydroxy polyethylene glycol and isophorone diisocyanate, react at 60-65° C. for 1-2 hours, add trimethylolpropane diacrylate or trimethylolpropane monoallyl ether, p-hydroxyanisole and dibutyltin dilaurate, stir evenly, and react at 80-85° C. for 4-4.5 hours to obtain a cross-linking agent containing a double bond;

[0008] A crosslinking agent A containing a double bond is prepared by reacting trimethylolpropane diacrylate; a crosslinking agent B containing a double bond is prepared by reacting trimethylolpropane monoallyl ether;

[0009] Step (2): baking the nano titanium dioxide at 120° C. for 7 to 8 hours, mixing with toluene diisocyanate after baking, stirring evenly with N,N-dimethylformamide, ultrasonicating for 1 to 2 hours under a nitrogen environment, adding dibutyltin dilaurate, ultrasonicating for 1 to 2 hours at 80 to 85° C., adding a crosslinking agent B containing a double bond, continuing to stir and react for 1 to 2 hours, collecting the product by centrifugation, washing and drying, and obtaining modified titanium dioxide;

[0010] Step (3): mixing a fluorocarbon resin, a solvent, modified titanium dioxide and a dispersant, stirring evenly, grinding to a fineness of less than 5 μm, adding a leveling agent and a defoaming agent, stirring and dispersing, and obtaining component A;

[0011] The isocyanate trimer, the crosslinking agent A containing a double bond or the crosslinking agent B containing a double bond, the initiator, the solvent and the drying agent are mixed and stirred to obtain component B;

[0012] Mix component A and component B, stir evenly, and obtain a fluorocarbon coating;

[0013] Step (4): Take a PET film as a carrier, coat a photocurable resin on one side of the PET film, roll and photocuring it to form a prism structure layer; then plate metal aluminum on the prism structure layer to form a reflective layer; coat a fluorocarbon coating on the other side of the PET film, and cure it at 80 to 90° C. to form a fluorine-containing layer to obtain a reflective film.

[0014] In this embodiment, in step (3), the specific amount of component A is, by mass, 40 to 50 parts of fluorocarbon resin, 15 to 20 parts of solvent, 20 to 30 parts of modified titanium dioxide, 0.5 to 1 part of dispersant, 0.3 to 0.5 part of leveling agent, and 0.3 to 0.5 part of defoaming agent;

[0015] The specific amount of component B is, by mass, 35-40 parts of isocyanate trimer, 10-15 parts of crosslinking agent A containing double bonds or crosslinking agent B containing double bonds, 0.1-0.5 parts of initiator, 0.05-0.1 parts of drying agent, and 30-35 parts of solvent;

[0016] Component A and component B are stirred and mixed in a mass ratio of (7-10):1.

[0017] In this embodiment, in step (2), the mass ratio of the nano titanium dioxide to toluene diisocyanate is 1:

[0018] (3-4); The mass ratio of the nano titanium dioxide to the cross-linking agent B containing double bonds is 1:(13-15).

[0019] In this embodiment, in step (1), the preparation steps of polyhydroxy polyethylene glycol are:

[0020] S1: Take 2 / 3 of the mass fraction of solid sodium hydroxide and prepare a sodium hydroxide aqueous solution with a mass fraction of 40-50%;

[0021] S2: Mix polyethylene glycol and tetra-n-butylammonium chloride, stir evenly, heat to 40-45°C, add epichlorohydrin, add 1 / 3 mass part of solid sodium hydroxide at 55-60°C, keep warm for 30-40min, then add sodium hydroxide aqueous solution, continue to react for 1-1.5h, cool to room temperature after the reaction, filter with chloroform, adjust to neutral with hydrochloric acid, and distill under reduced pressure to obtain polyethylene glycol glycidyl ether; mix polyethylene glycol glycidyl ether and deionized water, add concentrated sulfuric acid, hydrolyze at 25-30°C for 3-4h, adjust to neutral with sodium carbonate, and distill under reduced pressure to obtain polyhydroxy polyethylene glycol.

[0022] In this embodiment, the molar ratio of the polyethylene glycol, epichlorohydrin, solid sodium hydroxide and tetra-n-butylammonium chloride is 1:(2.1-2.3):3:(0.03-0.04); the pH value during hydrolysis is 5.5.

[0023] In this embodiment, in step (1), the molar ratio of the polyhydroxy polyethylene glycol to isophorone diisocyanate is 1:(4.2-4.5); the molar ratio of the polyhydroxy polyethylene glycol to trimethylolpropane diacrylate or trimethylolpropane monoallyl ether is 1:(2-2.3); the amount of p-hydroxyanisole is 0.6-0.8wt% of isophorone diisocyanate; and the amount of dibutyltin dilaurate is 0.5-0.8wt% of isophorone diisocyanate.

[0024] In this embodiment, in step (4), the coating thickness of the fluorocarbon coating is 8 to 10 μm, and the thickness of the PET film is 0.1 to 0.3 mm.

[0025] In this embodiment, the solvent is propylene glycol methyl ether acetate, and the initiator is potassium persulfate.

[0026] In this embodiment, the photovoltaic reflective film is prepared according to any one of the above methods for preparing a corrosion-resistant photovoltaic reflective film.

[0027] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0028] The invention discloses a corrosion-resistant photovoltaic reflective film and a preparation method thereof. The scheme uses a PET film as a carrier, coats a photocurable resin on one side of the PET film, rolls the PET film through a mold roller and then performs photocuring to form a prism structure layer, then plates metal aluminum on the prism structure layer to form a reflective layer, and finally coats a fluorocarbon coating on the other side of the PET film, and then cures the film to obtain a reflective film. The specific processing technology used in the preparation process is not limited, as long as the technical effect described in the application can be achieved. When the prism structure layer is actually processed, the photocurable resin can be coated on the surface of the mold roller and then transferred to the surface of the PET film to form a prism structure. The reflective layer can be plated with a metal layer through vacuum evaporation, magnetron sputtering, electroplating and other processes, and the plating material can be selected from aluminum, silver and the like to achieve a reflective effect. The photocurable resin can be selected from polyacrylate or other resins that can be photocured. The thickness of the reflective layer and the prism structure layer can be adjusted according to actual needs, and no further details are given here.

[0029] Conventional reflective film generally needs to be bonded with EVA film to achieve bonding, so that the reflective film is attached to the backboard or component. The present invention adjusts the formula of fluorocarbon coating and uses fluorocarbon coating to apply to the surface of PET film, which can protect the PET film on the one hand and improve the bonding performance between the PET film and the subsequent EVA film on the other hand. During the preparation, polyhydroxy polyethylene glycol, trimethylolpropane diacrylate or trimethylolpropane monoallyl ether are first used as raw materials to generate a polyurethane acrylate crosslinking agent, and the isocyanate of isophorone diisocyanate is used to form a polyurethane acrylate crosslinking agent. The acid ester group realizes the bridging of the hydroxyl groups of polyhydroxy polyethylene glycol and the hydroxyl groups of trimethylolpropane diacrylate, and the double bonds are introduced by using trimethylolpropane diacrylate or trimethylolpropane monoallyl ether to generate a polyurethane acrylate cross-linking agent containing double bonds. This component is introduced into the fluorocarbon coating, and an interpenetrating network is formed in the fluorocarbon coating under the action of an initiator. The cross-linking network formed by the fluorocarbon resin and the isocyanate trimer can effectively improve the corrosion resistance of the fluorocarbon coating, and at the same time can improve the bonding performance between the PET film and the EVA film.

[0030] At the same time, the polyurethane acrylate crosslinking agent containing double bonds contains a large amount of isocyanate groups, which can replace part of the curing agent and be compounded with the isocyanate trimer to achieve curing, making the effect of the fluorocarbon coating more excellent.

[0031] On this basis, the present application uses toluene diisocyanate to modify titanium dioxide, and then uses isocyanate groups to bridge trimethylolpropane monoallyl ether. While improving the dispersibility of titanium dioxide, the isocyanate groups and double bonds on the surface of titanium dioxide can also participate in the cross-linking of the system, and the UV resistance of the fluorocarbon coating is also improved.

[0032] The invention discloses a corrosion-resistant photovoltaic reflective film and a preparation method thereof. The scheme sets the structure of the reflective film as a reflective layer-prism structure layer, a PET film-fluorocarbon coating, and then the film is bonded to a back plate with an EVA adhesive film. The application adjusts the formula and specific preparation process of the fluorocarbon coating. The prepared fluorocarbon coating not only has excellent aging resistance and corrosion resistance, but also the presence of the fluorocarbon coating can improve the bonding performance between the EVA adhesive film and the PET film, and the practicability is high. DETAILED DESCRIPTION

[0033] The following is a preferred implementation of the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. For ordinary technicians in this technical field, all other embodiments obtained by ordinary technicians in this field without creative work without departing from the principle of the embodiment of the present invention are within the scope of protection of the present invention.

[0034] In this embodiment, the preparation steps of polyhydroxy polyethylene glycol are:

[0035] S1: Take 2 / 3 of the mass fraction of solid sodium hydroxide and prepare a sodium hydroxide aqueous solution with a mass fraction of 40%;

[0036] S2: 0.1 mol of polyethylene glycol and tetra-n-butylammonium chloride are mixed, stirred evenly, heated to 45°C, 0.22 mol of epichlorohydrin is added, 1 / 3 mass part of solid sodium hydroxide is added at 55°C, the reaction is kept warm for 40 minutes, and then an aqueous sodium hydroxide solution is added, and the reaction is continued for 1.2 hours. After the reaction is completed, it is cooled to room temperature, chloroform is filtered, hydrochloric acid is adjusted to neutral, and distilled under reduced pressure to obtain polyethylene glycol glycidyl ether; polyethylene glycol glycidyl ether and deionized water are mixed, concentrated sulfuric acid is added, the pH is 5.5, and hydrolyzed at 25°C for 4 hours. Sodium carbonate is adjusted to neutral, and distilled under reduced pressure to obtain polyhydroxy polyethylene glycol.

[0037] The molar ratio of the polyethylene glycol, epichlorohydrin, solid sodium hydroxide and tetra-n-butylammonium chloride is 1:2.2:3:0.03.

[0038] In this embodiment, the solvent is propylene glycol methyl ether acetate, the nano titanium dioxide model is P25, provided by Bayer (China) Co., Ltd.; the polyethylene glycol is PEG-400; the fluorocarbon resin is ETERFLON4101, provided by Changxing Chemical Industry Co., Ltd., with a hydroxyl value of 56 mgKOH / g and a solid content of 60%; the dispersant is BYK-P-104s; the leveling agent is TEGO100; the defoamer is SF561; the drying agent is dibutyltin dilaurate; the initiator is potassium persulfate; the isocyanate trimer is HDI trimer N3390, provided by Covestro. The EVA film is Svek SV-15297.

[0039] Embodiment 1: A method for preparing a corrosion-resistant photovoltaic reflective film, comprising the following steps:

[0040] Step (1): 0.1 mol of polyhydroxy polyethylene glycol and 0.42 mol of isophorone diisocyanate are mixed, reacted at 60° C. for 2 h, 0.22 mol of trimethylolpropane diacrylate or trimethylolpropane monoallyl ether, p-hydroxyanisole and dibutyltin dilaurate are added, stirred evenly, and reacted at 80° C. for 4.5 h to obtain a cross-linking agent containing double bonds.

[0041] A crosslinking agent A containing a double bond is prepared by reacting trimethylolpropane diacrylate; a crosslinking agent B containing a double bond is prepared by reacting trimethylolpropane monoallyl ether; the amount of p-hydroxyanisole used is 0.6wt% of isophorone diisocyanate; and the amount of dibutyltin dilaurate used is 0.5wt% of isophorone diisocyanate.

[0042] Step (2): bake the nano titanium dioxide at 120°C for 7 hours, mix it with toluene diisocyanate after baking, stir it evenly with N,N-dimethylformamide, ultrasonicate it under nitrogen environment for 1 hour, then add dibutyltin dilaurate, ultrasonicate it at 80°C for 2 hours, then add the cross-linking agent B containing double bonds prepared in step (1), continue to stir the reaction for 1 hour, collect the product by centrifugation, wash and dry it to obtain modified titanium dioxide.

[0043] The mass ratio of the nano titanium dioxide to toluene diisocyanate is 1:3.5; the mass ratio of the nano titanium dioxide to the crosslinking agent B containing double bonds is 1:15. The amount of dibutyltin dilaurate used is 0.15wt% of toluene diisocyanate.

[0044] Step (3): by weight, 45 parts of fluorocarbon resin, 18 parts of solvent, 25 parts of modified titanium dioxide and 0.5 parts of dispersant are mixed, stirred evenly, ground to a fineness of less than 5 μm, 0.3 parts of leveling agent and 0.3 parts of defoaming agent are added, stirred and dispersed, and component A is obtained.

[0045] In parts by mass, 38 parts of isocyanate trimer, 13 parts of the cross-linking agent A containing double bonds prepared in step (1), 0.5 parts of initiator, 35 parts of solvent and 0.1 parts of drying agent are mixed and stirred evenly to obtain component B.

[0046] Component A and component B are mixed in a mass ratio of 8:1, stirred evenly, and a fluorocarbon coating is obtained.

[0047] Step (4): Take a PET film as a carrier, coat a light-curable resin on one side of the PET film, roll and then photo-curing to form a prism structure layer; then plate metal aluminum on the prism structure layer to form a reflective layer; coat a fluorocarbon coating on the other side of the PET film, and cure at 90° C. to form a fluorine-containing layer to obtain a reflective film. The coating thickness of the fluorocarbon coating is 10 μm, and the thickness of the PET film is 0.2 mm.

[0048] Embodiment 2: A method for preparing a corrosion-resistant photovoltaic reflective film, comprising the following steps:

[0049] Step (1): 0.1 mol of polyhydroxy polyethylene glycol and 0.42 mol of isophorone diisocyanate are mixed, reacted at 65° C. for 1.5 h, 0.22 mol of trimethylolpropane diacrylate or trimethylolpropane monoallyl ether, p-hydroxyanisole and dibutyltin dilaurate are added, stirred evenly, and reacted at 85° C. for 4.5 h to obtain a cross-linking agent containing double bonds.

[0050] A crosslinking agent A containing a double bond is prepared by reacting trimethylolpropane diacrylate; a crosslinking agent B containing a double bond is prepared by reacting trimethylolpropane monoallyl ether; the amount of p-hydroxyanisole used is 0.6wt% of isophorone diisocyanate; and the amount of dibutyltin dilaurate used is 0.5wt% of isophorone diisocyanate.

[0051] Step (2): bake the nano titanium dioxide at 120°C for 7 hours, mix it with toluene diisocyanate after baking, stir it evenly with N,N-dimethylformamide, ultrasonicate it under nitrogen environment for 1 to 2 hours, then add dibutyltin dilaurate, ultrasonicate it at 85°C for 1.5 hours, then add the cross-linking agent B containing double bonds prepared in step (1), continue to stir the reaction for 1 to 2 hours, collect the product by centrifugation, wash and dry it to obtain modified titanium dioxide.

[0052] The mass ratio of the nano titanium dioxide to toluene diisocyanate is 1:3.5; the mass ratio of the nano titanium dioxide to the crosslinking agent B containing double bonds is 1:15. The amount of dibutyltin dilaurate used is 0.15wt% of toluene diisocyanate.

[0053] Step (3): by weight, 45 parts of fluorocarbon resin, 18 parts of solvent, 25 parts of modified titanium dioxide and 0.5 parts of dispersant are mixed, stirred evenly, ground to a fineness of less than 5 μm, 0.3 parts of leveling agent and 0.3 parts of defoaming agent are added, stirred and dispersed, and component A is obtained.

[0054] In parts by mass, 38 parts of isocyanate trimer, 14 parts of the cross-linking agent A containing double bonds prepared in step (1), 0.5 parts of initiator, 35 parts of solvent and 0.1 parts of drying agent are mixed and stirred evenly to obtain component B.

[0055] Component A and component B are mixed in a mass ratio of 8:1, stirred evenly, and a fluorocarbon coating is obtained.

[0056] Step (4): Take a PET film as a carrier, coat a light-curable resin on one side of the PET film, roll and then photo-curing to form a prism structure layer; then plate metal aluminum on the prism structure layer to form a reflective layer; coat a fluorocarbon coating on the other side of the PET film, and cure at 90° C. to form a fluorine-containing layer to obtain a reflective film. The coating thickness of the fluorocarbon coating is 10 μm, and the thickness of the PET film is 0.2 mm.

[0057] Embodiment 3: A method for preparing a corrosion-resistant photovoltaic reflective film, comprising the following steps:

[0058] Step (1): 0.1 mol of polyhydroxy polyethylene glycol and 0.42 mol of isophorone diisocyanate are mixed, reacted at 65° C. for 1 h, 0.22 mol of trimethylolpropane diacrylate or trimethylolpropane monoallyl ether, p-hydroxyanisole and dibutyltin dilaurate are added, stirred evenly, and reacted at 85° C. for 4 h to obtain a cross-linking agent containing double bonds.

[0059] A crosslinking agent A containing a double bond is prepared by reacting trimethylolpropane diacrylate; a crosslinking agent B containing a double bond is prepared by reacting trimethylolpropane monoallyl ether; the amount of p-hydroxyanisole used is 0.6wt% of isophorone diisocyanate; and the amount of dibutyltin dilaurate used is 0.5wt% of isophorone diisocyanate.

[0060] Step (2): bake the nano titanium dioxide at 120°C for 7 hours, mix it with toluene diisocyanate after baking, stir it evenly with N,N-dimethylformamide, ultrasonicate it under nitrogen environment for 2 hours, then add dibutyltin dilaurate, ultrasonicate it at 85°C for 1 hour, then add the cross-linking agent B containing double bonds prepared in step (1), continue stirring and reacting for 2 hours, collect the product by centrifugation, wash and dry it to obtain modified titanium dioxide.

[0061] The mass ratio of the nano titanium dioxide to toluene diisocyanate is 1:3.5; the mass ratio of the nano titanium dioxide to the crosslinking agent B containing double bonds is 1:15. The amount of dibutyltin dilaurate used is 0.15wt% of toluene diisocyanate.

[0062] Step (3): by weight, 45 parts of fluorocarbon resin, 18 parts of solvent, 25 parts of modified titanium dioxide and 0.5 parts of dispersant are mixed, stirred evenly, ground to a fineness of less than 5 μm, 0.3 parts of leveling agent and 0.3 parts of defoaming agent are added, stirred and dispersed, and component A is obtained.

[0063] In parts by mass, 38 parts of isocyanate trimer, 15 parts of the cross-linking agent A containing double bonds prepared in step (1), 0.5 parts of an initiator, 35 parts of a solvent and 0.1 parts of a drying agent are mixed and stirred uniformly to obtain component B.

[0064] Component A and component B are mixed in a mass ratio of 8:1, stirred evenly, and a fluorocarbon coating is obtained.

[0065] Step (4): Take a PET film as a carrier, coat a light-curable resin on one side of the PET film, roll and then photo-curing to form a prism structure layer; then plate metal aluminum on the prism structure layer to form a reflective layer; coat a fluorocarbon coating on the other side of the PET film, and cure at 90° C. to form a fluorine-containing layer to obtain a reflective film. The coating thickness of the fluorocarbon coating is 10 μm, and the thickness of the PET film is 0.2 mm.

[0066] Example 4: The formula of the fluorocarbon coating is adjusted based on Example 3, and the other steps remain unchanged.

[0067] A method for preparing a corrosion-resistant photovoltaic reflective film comprises the following steps:

[0068] Step (1): 0.1 mol of polyhydroxy polyethylene glycol and 0.42 mol of isophorone diisocyanate were mixed, reacted at 65° C. for 1 h, 0.22 mol of trimethylolpropane monoallyl ether, p-hydroxyanisole and dibutyltin dilaurate were added, stirred evenly, and reacted at 85° C. for 4 h to obtain a crosslinking agent B containing a double bond.

[0069] The amount of p-hydroxyanisole used is 0.6wt% of isophorone diisocyanate; the amount of dibutyltin dilaurate used is 0.5wt% of isophorone diisocyanate.

[0070] Step (2): bake the nano titanium dioxide at 120°C for 7 hours, mix it with toluene diisocyanate after baking, stir it evenly with N,N-dimethylformamide, ultrasonicate it under nitrogen environment for 2 hours, then add dibutyltin dilaurate, ultrasonicate it at 85°C for 1 hour, then add the cross-linking agent B containing double bonds prepared in step (1), continue stirring and reacting for 2 hours, collect the product by centrifugation, wash and dry it to obtain modified titanium dioxide.

[0071] The mass ratio of the nano titanium dioxide to toluene diisocyanate is 1:3.5; the mass ratio of the nano titanium dioxide to the crosslinking agent B containing double bonds is 1:15. The amount of dibutyltin dilaurate used is 0.15wt% of toluene diisocyanate.

[0072] Step (3): by weight, 45 parts of fluorocarbon resin, 18 parts of solvent, 25 parts of modified titanium dioxide and 0.5 parts of dispersant are mixed, stirred evenly, ground to a fineness of less than 5 μm, 0.3 parts of leveling agent and 0.3 parts of defoaming agent are added, stirred and dispersed, and component A is obtained.

[0073] In parts by mass, 38 parts of isocyanate trimer, 15 parts of the cross-linking agent B containing a double bond prepared in step (1), 0.5 parts of an initiator, 35 parts of a solvent and 0.1 parts of a drying agent are mixed and stirred uniformly to obtain component B.

[0074] Component A and component B are mixed in a mass ratio of 8:1, stirred evenly, and a fluorocarbon coating is obtained.

[0075] Step (4): Take a PET film as a carrier, coat a light-curable resin on one side of the PET film, roll and then photo-curing to form a prism structure layer; then plate metal aluminum on the prism structure layer to form a reflective layer; coat a fluorocarbon coating on the other side of the PET film, and cure at 90° C. to form a fluorine-containing layer to obtain a reflective film. The coating thickness of the fluorocarbon coating is 10 μm, and the thickness of the PET film is 0.2 mm.

[0076] Comparative Example 1: A control experiment was conducted based on Example 3, wherein the nano-titanium dioxide was modified only by toluene diisocyanate, and the other steps remained unchanged.

[0077] A method for preparing a corrosion-resistant photovoltaic reflective film comprises the following steps:

[0078] Step (1): 0.1 mol of polyhydroxy polyethylene glycol and 0.42 mol of isophorone diisocyanate were mixed, reacted at 65° C. for 1 h, 0.22 mol of trimethylolpropane diacrylate, p-hydroxyanisole and dibutyltin dilaurate were added, stirred evenly, and reacted at 85° C. for 4 h to obtain a crosslinking agent A containing a double bond.

[0079] The amount of p-hydroxyanisole used is 0.6wt% of isophorone diisocyanate; the amount of dibutyltin dilaurate used is 0.5wt% of isophorone diisocyanate.

[0080] Step (2): bake the nano titanium dioxide at 120°C for 7 hours, mix it with toluene diisocyanate after baking, stir it evenly with N,N-dimethylformamide, ultrasonicate it under nitrogen environment for 2 hours, then add dibutyltin dilaurate, ultrasonicate it at 85°C for 1 hour, collect the product by centrifugation, wash and dry it to obtain modified titanium dioxide.

[0081] The mass ratio of the nano titanium dioxide to toluene diisocyanate is 1:3.5. The amount of dibutyltin dilaurate is 0.15wt% of toluene diisocyanate.

[0082] Step (3): by weight, 45 parts of fluorocarbon resin, 18 parts of solvent, 25 parts of modified titanium dioxide and 0.5 parts of dispersant are mixed, stirred evenly, ground to a fineness of less than 5 μm, 0.3 parts of leveling agent and 0.3 parts of defoaming agent are added, stirred and dispersed, and component A is obtained.

[0083] In parts by mass, 38 parts of isocyanate trimer, 15 parts of the cross-linking agent A containing double bonds prepared in step (1), 0.5 parts of initiator, 35 parts of solvent and 0.1 parts of drying agent are mixed and stirred uniformly to obtain component B.

[0084] Component A and component B are mixed in a mass ratio of 8:1, stirred evenly, and a fluorocarbon coating is obtained.

[0085] Step (4): Take a PET film as a carrier, coat a light-curable resin on one side of the PET film, roll and then photo-curing to form a prism structure layer; then plate metal aluminum on the prism structure layer to form a reflective layer; coat a fluorocarbon coating on the other side of the PET film, and cure at 90° C. to form a fluorine-containing layer to obtain a reflective film. The coating thickness of the fluorocarbon coating is 10 μm, and the thickness of the PET film is 0.2 mm.

[0086] Comparative Example 2: A control experiment was conducted based on Example 3, except that a cross-linking agent containing double bonds was not introduced, the formula of the fluorocarbon coating was adjusted, and the other steps remained unchanged.

[0087] A method for preparing a corrosion-resistant photovoltaic reflective film comprises the following steps:

[0088] Step (1): bake the nano titanium dioxide at 120°C for 7 hours, mix it with toluene diisocyanate after baking, stir it evenly with N,N-dimethylformamide, ultrasonicate it under nitrogen environment for 2 hours, then add dibutyltin dilaurate, ultrasonicate it at 85°C for 1 hour, collect the product by centrifugation, wash and dry it to obtain modified titanium dioxide.

[0089] The mass ratio of the nano titanium dioxide to toluene diisocyanate is 1:3.5. The amount of dibutyltin dilaurate is 0.15wt% of toluene diisocyanate.

[0090] Step (3): by weight, 45 parts of fluorocarbon resin, 18 parts of solvent, 25 parts of modified titanium dioxide and 0.5 parts of dispersant are mixed, stirred evenly, ground to a fineness of less than 5 μm, 0.3 parts of leveling agent and 0.3 parts of defoaming agent are added, stirred and dispersed, and component A is obtained.

[0091] 48 parts of isocyanate trimer, 35 parts of solvent and 0.1 parts of drier were mixed and stirred uniformly to obtain component B, based on parts by mass.

[0092] Component A and component B are mixed in a mass ratio of 8:1, stirred evenly, and a fluorocarbon coating is obtained.

[0093] Step (4): Take a PET film as a carrier, coat a light-curable resin on one side of the PET film, roll and then photo-curing to form a prism structure layer; then plate metal aluminum on the prism structure layer to form a reflective layer; coat a fluorocarbon coating on the other side of the PET film, and cure at 90° C. to form a fluorine-containing layer to obtain a reflective film. The coating thickness of the fluorocarbon coating is 10 μm, and the thickness of the PET film is 0.2 mm.

[0094] Detection experiment:

[0095] 1. According to the methods disclosed in Examples 1 to 4 and Comparative Examples 1 to 2, a fluorocarbon coating was coated on one side of the PET film with a coating thickness of 10 μm and cured at 90°C to obtain a test sample. The adhesion of the fluorocarbon coating was tested by the cross-hatch method disclosed in GB / T9286 and the adhesion grade was recorded. Aging test in a UV aging box with a cumulative irradiance of 120 kWh / m 2 , record the yellowing ΔY.

[0096] 2. According to the method disclosed in Examples 1 to 4 and Comparative Examples 1 to 2, one side of the PET film was coated with a fluorocarbon coating with a coating thickness of 10 μm and cured at 90°C. The PET film, EVA film, and PET film were then stacked in order, with one side of the fluorocarbon coating in contact with the EVA film. The films were hot-pressed and cured at a temperature of 150°C and a pressure of 10 MPa. The peel strength of the PET film and the EVA film was tested with reference to the method disclosed in GB / T2791, and the peeling speed was 100 mm / min.

[0097]

[0098] Conclusion: The present invention discloses a corrosion-resistant photovoltaic reflective film and a preparation method thereof. The reflective film is configured with a reflective layer-prism structure layer, a PET film-fluorocarbon coating, and then bonded to a back panel with an EVA adhesive film. The present application adjusts the formula and specific preparation process of the fluorocarbon coating. The prepared fluorocarbon coating not only has excellent aging resistance and corrosion resistance, but the presence of the fluorocarbon coating can also improve the bonding performance between the EVA adhesive film and the PET film, and has high practicality.

[0099] Finally, it should be noted that the above is only a preferred embodiment of the present invention, but the protection scope of this application is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the spirit and principle of the present invention and within the technical scope disclosed in this application should be included in the protection scope of this application; in the absence of conflict, the embodiments of this application and the features in the embodiments can be combined with each other. Therefore, the protection scope of this application shall be based on the protection scope of the claims.

Claims

1. A method for preparing a corrosion-resistant photovoltaic reflective film, characterized in that: The following steps are involved: Step (1): Mix polyhydroxy polyethylene glycol and isophorone diisocyanate, react at 60-65° C. for 1-2 hours, add trimethylolpropane diacrylate or trimethylolpropane monoallyl ether, p-hydroxyanisole and dibutyltin dilaurate, stir evenly, and react at 80-85° C. for 4-4.5 hours to obtain a cross-linking agent containing a double bond; A crosslinking agent A containing a double bond is prepared by reacting trimethylolpropane diacrylate; a crosslinking agent B containing a double bond is prepared by reacting trimethylolpropane monoallyl ether; Step (2): baking the nano titanium dioxide at 120° C. for 7 to 8 hours, mixing with toluene diisocyanate after baking, stirring evenly with N,N-dimethylformamide, ultrasonicating for 1 to 2 hours under a nitrogen environment, adding dibutyltin dilaurate, ultrasonicating for 1 to 2 hours at 80 to 85° C., adding a crosslinking agent B containing a double bond, continuing to stir and react for 1 to 2 hours, collecting the product by centrifugation, washing and drying, and obtaining modified titanium dioxide; Step (3): mixing a fluorocarbon resin, a solvent, modified titanium dioxide and a dispersant, stirring evenly, grinding to a fineness of less than 5 μm, adding a leveling agent and a defoaming agent, stirring and dispersing, and obtaining component A; The isocyanate trimer, the crosslinking agent A containing a double bond or the crosslinking agent B containing a double bond, the initiator, the solvent and the drying agent are mixed and stirred to obtain component B; Mix component A and component B, stir evenly, and obtain a fluorocarbon coating; Step (4): Take a PET film as a carrier, coat a photocurable resin on one side of the PET film, roll and photocuring it to form a prism structure layer; then plate metal aluminum on the prism structure layer to form a reflective layer; coat a fluorocarbon coating on the other side of the PET film, and cure it at 80 to 90° C. to form a fluorine-containing layer to obtain a reflective film.

2. The method for preparing a corrosion-resistant photovoltaic reflective film according to claim 1, characterized in that: In step (3), the specific amount of component A is, by mass, 40 to 50 parts of fluorocarbon resin, 15 to 20 parts of solvent, 20 to 30 parts of modified titanium dioxide, 0.5 to 1 part of dispersant, 0.3 to 0.5 part of leveling agent, and 0.3 to 0.5 part of defoaming agent; The specific amount of component B is, by mass, 35-40 parts of isocyanate trimer, 10-15 parts of crosslinking agent A containing double bonds or crosslinking agent B containing double bonds, 0.1-0.5 parts of initiator, 0.05-0.1 parts of drying agent, and 30-35 parts of solvent; Component A and component B are stirred and mixed in a mass ratio of (7-10):

1.

3. The method for preparing a corrosion-resistant photovoltaic reflective film according to claim 1, characterized in that: In step (2), the mass ratio of the nano-titanium dioxide to toluene diisocyanate is 1:(3-4); the mass ratio of the nano-titanium dioxide to the cross-linking agent B containing double bonds is 1:(13-15).

4. The method for preparing a corrosion-resistant photovoltaic reflective film according to claim 1, characterized in that: In step (1), the preparation steps of polyhydroxy polyethylene glycol are: S1: Take 2 / 3 of the mass fraction of solid sodium hydroxide and prepare a sodium hydroxide aqueous solution with a mass fraction of 40-50%; S2: Mix polyethylene glycol and tetra-n-butylammonium chloride, stir evenly, heat to 40-45°C, add epichlorohydrin, add 1 / 3 mass part of solid sodium hydroxide at 55-60°C, keep warm for 30-40min, then add sodium hydroxide aqueous solution, continue to react for 1-1.5h, cool to room temperature after the reaction, filter with chloroform, adjust to neutral with hydrochloric acid, and distill under reduced pressure to obtain polyethylene glycol glycidyl ether; mix polyethylene glycol glycidyl ether and deionized water, add concentrated sulfuric acid, hydrolyze at 25-30°C for 3-4h, adjust to neutral with sodium carbonate, and distill under reduced pressure to obtain polyhydroxy polyethylene glycol.

5. The method for preparing a corrosion-resistant photovoltaic reflective film according to claim 4, characterized in that: The molar ratio of the polyethylene glycol, epichlorohydrin, solid sodium hydroxide and tetra-n-butylammonium chloride is 1:(2.1-2.3):3: (0.03~0.04)。 6. The method for preparing a corrosion-resistant photovoltaic reflective film according to claim 1, characterized in that: In step (1), the molar ratio of the polyhydroxy polyethylene glycol to isophorone diisocyanate is 1:(4.2-4.5); the molar ratio of the polyhydroxy polyethylene glycol to trimethylolpropane diacrylate or trimethylolpropane monoallyl ether is 1: (2~2.3); the amount of p-hydroxyanisole is 0.6~0.8wt% of isophorone diisocyanate; the amount of dibutyltin dilaurate is 0.5~0.8wt% of isophorone diisocyanate.

7. The method for preparing a corrosion-resistant photovoltaic reflective film according to claim 1, characterized in that: In step (4), the coating thickness of the fluorocarbon coating is 8 to 10 μm, and the thickness of the PET film is 0.1 to 0.3 mm.

8. The method for preparing a corrosion-resistant photovoltaic reflective film according to claim 1, characterized in that: The solvent is propylene glycol methyl ether acetate, and the initiator is potassium persulfate.

9. A photovoltaic reflective film prepared according to the method for preparing a corrosion-resistant photovoltaic reflective film according to any one of claims 1 to 8.